Wells’ syndrome associated with eosinophilic granulomatosis with polyangiitis − A case report - Radević, Tatjana; Kandolf Sekulović, Lidija; Ristić, Gorica G.; Mijušković, Željko P. (Vojnosanitetski pregled, 2021)
Introduction. Wells` syndrome (eosinophilic cellulitis) is a chronic, recurrent disease characterized by episodes of erythematous and edematous plaques or nodules with occasional development of hemorrhagic bullae on the trunk and limbs. Eosinophilic granulomatosis with polyangiitis, formerly known as Churg-Strauss syndrome, is a specific variant of the group of diseases characterized by necrotizing vasculitis of small to medium-sized blood vessels affecting multiple organ systems. The association of Wells` syndrome and eosinophilic granulomatosis with polyangiitis is very rare, and to our knowledge has been reported in only ten patients. Case report. We present a case of a 34-year-old woman with a 3-year history of periodical onset of erythematous plaques on the trunk and edematous plaques clinically resembling cellulitis on her lower limbs. The patient reported a one-year history of asthma, rhinosinusitis, and nasal polyposis. Skin biopsy revealed the presence of diffuse eosinophilic infiltrates in the dermis accompanied by characteristic “flame figures”. Further investigation showed peripheral blood eosinophilia (22.6%), bilateral maxillary sinusitis, presence of eosinophil infiltrates and microabscesses in the bronchial wall, and pericapillary eosinophil infiltrates in the pulmonary interstitium shown by bronchoscopy and transbronchial biopsy, respectively. Treatment was started with methylprednisolone 0.5 mg/kg/day, and the dose was gradually tapered for the following twelve weeks. Complete remission of skin changes was achieved, but new lesions appeared in the past two years, which required repeated treatment. Conclusion. Association of these syndromes is unusual and may be based on the common pathogenetic background. We hypothesize that Wells` syndrome could be a stage preceding eosinophilic granulomatosis with polyangiitis,  and that patients should be evaluated for eosinophilic granulomatosis with polyangiitis, since these two diseases overlap in clinical and laboratory findings.
Keywords: biopsy; churg-strauss syndrome; diagnosis; eosinophilia; wells syndrome; therapeutics; treatment outcome.